1995
DOI: 10.2307/146188
|View full text |Cite
|
Sign up to set email alerts
|

Human Capital and Information: The Employer Size-Wage Effect

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. University of Wisconsin Press andThe Board of Regents of the University of Wisconsin System are collaborating with JSTOR to digitize, preserve and extend access to The Journal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
8

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(44 citation statements)
references
References 19 publications
2
34
0
8
Order By: Relevance
“…Similar observations have been made in other countries (e.g. Bell (1998) for the UK; Reilly (1995) in Canada), but there is much evidence that this is due to the fact that workers with higher ability are given the best technologies to use. Entorf and Kramarz (1997) emphasise that the cross-sectional association in France disappears once fixed effects have been controlled for.…”
Section: Wagessupporting
confidence: 80%
“…Similar observations have been made in other countries (e.g. Bell (1998) for the UK; Reilly (1995) in Canada), but there is much evidence that this is due to the fact that workers with higher ability are given the best technologies to use. Entorf and Kramarz (1997) emphasise that the cross-sectional association in France disappears once fixed effects have been controlled for.…”
Section: Wagessupporting
confidence: 80%
“…Our result with respect to size does not explain the hospital premium, but suggests that the explanation may involve many of the same factors driving the economywide employer size effect. And evidence suggests some of the size premium reflects higher skilled workers among large employers (e.g., Brown and Medoff, 1989;Reilly, 1995).…”
Section: Union and Employer Size Effects On The Hospital Premiummentioning
confidence: 99%
“…Thus, future study on this topic in China should try to collect data in more creative ways, similar to what has been done in other countries during the past several decades. 2 This brief summary is mainly based on six pieces of literature: Brown and Medoff (1989), Kalleberg and Buren (1992), Reilly (1995), Kalleberg and Buren (1996), Troske (1999), andHollister (2004). 3 An exception is the research conducted by Walder (1992), in which workplace size was indeed found to be a significant predictor for workers' job benefits in the city of Tianjin.…”
Section: Discussionmentioning
confidence: 99%